2015
DOI: 10.1097/jps.0000000000000049
|View full text |Cite
|
Sign up to set email alerts
|

After the ABCs

Abstract: Background: The effects of trauma do not end after resuscitation. The Screening Tool for Early Predictors of Post Traumatic Stress Disorder (STEPP) is validated for pediatric trauma victims and their parents. This would help identifying children and caregivers at risk for posttraumatic stress disorder (PTSD) and highlight mechanisms of trauma that increase risk.Methods: A retrospective review of 142 children and parents admitted to a Level I pediatric trauma center was completed. Variables of age, gender, inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
2
2
0
Order By: Relevance
“…Similar to a previous study that evaluated this screening program in the first year of implementation (Gill-Appiott & Murphy, 2015), the current findings offer evidence that such screening continues to be feasible 4 years after initiation of this program. As noted above, previous studies examining implementation of standardized screening, including the STEPP, found rates of completed screen between 12 and 86% (Hix-Small et al, 2007; Ward-Begnoche et al, 2006; Zebrack et al, 2015).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Similar to a previous study that evaluated this screening program in the first year of implementation (Gill-Appiott & Murphy, 2015), the current findings offer evidence that such screening continues to be feasible 4 years after initiation of this program. As noted above, previous studies examining implementation of standardized screening, including the STEPP, found rates of completed screen between 12 and 86% (Hix-Small et al, 2007; Ward-Begnoche et al, 2006; Zebrack et al, 2015).…”
Section: Discussionsupporting
confidence: 84%
“…Despite high rates of screen completion, nearly 30% of eligible patients did not complete the screen, a finding similar to the roughly 20% of those who did not complete screens in a study of the initial implementation of this program (Gill-Appiott & Murphy, 2015). In addition, nearly 30% of patients who screened positively did not have a psychology consultation.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations